KEPEMIMPINAN TRANSFORMATIF DALAM PENINGKATAN BUDAYA ETOS KERJA PEDISIPLINAN GURU DI MTSN 2 JOMBANG - Kurnia Ridhwan Abdillah; Moh Syamsul Falah (Jurnal Manajemen Pendidikan, 2026)
The principal's leadership plays a strategic role in shaping the work ethic culture and discipline of teachers, particularly in Islamic educational institutions that are required to meet academic quality standards while upholding religious values. This study aims to describe the form of transformational leadership at MTsN 2 Jombang, analyze the work ethic culture of teacher discipline, and examine the role of transformational leadership in improving the work ethic culture and discipline of teachers at the institution. This study employed a qualitative method with a naturalistic-descriptive approach and a case study design. Data were collected through in-depth interviews, participatory observation, and documentation study involving the principal, teachers, and educational support staff selected through purposive sampling. Data analysis followed the interactive analysis model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing and verification. The findings indicate that transformational leadership was implemented comprehensively through four dimensions: consistent role modeling (idealized influence), inspirational motivation grounded in prophetic values (inspirational motivation), intellectual stimulation through open communication (intellectual stimulation), and individualized consideration.